Shared service centres in the Czech public service administration - advantage and risks of their implementation - Pelikánová, Šárka; Vostrovská, Zdenka, 1956-; Khorel, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
The baccalaureate thesis examines shared service centres, their implementation in the Czech public services administration and the related risks. The goal of this thesis is to provide an overview of the shared service centres, their role within the public service administration with a focus on the consequences of their implementation for the Czech public service administration. The first chapter describes the international competitiveness prospects of the Czech Republic for 2012-2020, as well as the Effective Public Services Administration project which supports the implementation of shared service centers. The second chapter examines the potential for optimization of institutional processes with a focus on shared service centres and the various types of support services most commonly provided by these. The third chapter describes the public services shared service centres implementation process which took place in Austria and the Netherlands, followed by an analysis and comparison of the Czech, Austrian and Dutch public services administration. The fourth chapter provides an outline of the current shared service centres implementation status in public service administration, as well as the author's view of some of the expected resulting advantages and risks. The thesis is based on information obtained from available literature, internet sources, a case study on the implementation of shared service centres by the Dutch Ministry of Justice, data made public by SAP, Eurostat and OECD.
Vedoucí práce: Zdenka Vostrovská
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: národní hospodářství [obor bakal. práce]; bakalářské práce; bachelor's theses